2002
DOI: 10.1177/104973150201200203
|View full text |Cite
|
Sign up to set email alerts
|

Couples Who Care: The Effectiveness of a Psychoeducational Group Intervention for HIV Serodiscordant Couples

Abstract: Objective: The pilot study examined the effectiveness of a psychoeducational group intervention for HIV/AIDS, serodiscordant, heterosexual couples. Method: A quasi-experimental pretest posttest design was used to examine depression, anxiety, and marital satisfaction of couples in which one spouse was HIV positive and the other spouse was negative. Results: Univariate analyses of covariance indicated significant differences between the experimental and comparison groups on each dependent variable. Effect sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 20 publications
2
33
0
1
Order By: Relevance
“…Successful HIV prevention strategies employ multisession interventions emphasizing sexual communication, problem solving, and negotiation skills, including 'homework' to practice skills (El-Bassel et al, 2001;El-Bassel et al, 2003;Pomeroy et al, 2002). Our four-session intervention (Table I) provided didactic information on HIV/AIDS and risk reduction strategies, relapse prevention and skills training through role-playing and rehearsal in small groups.…”
Section: The Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful HIV prevention strategies employ multisession interventions emphasizing sexual communication, problem solving, and negotiation skills, including 'homework' to practice skills (El-Bassel et al, 2001;El-Bassel et al, 2003;Pomeroy et al, 2002). Our four-session intervention (Table I) provided didactic information on HIV/AIDS and risk reduction strategies, relapse prevention and skills training through role-playing and rehearsal in small groups.…”
Section: The Interventionmentioning
confidence: 99%
“…Because previous studies of partner referral for HIV and other STIs report low referral rates (Machekano et al, 2000;Nuwaha et al, 2000) the feasibility of our approach was unknown. Additionally, when the study began there were no reported group-based interventions for discordant couples (Kalichman et al, 2002;Pomeroy et al, 2002). This paper describes the feasibility of the intervention and results regarding condom use.…”
Section: Introductionmentioning
confidence: 96%
“…The small body of literature that goes beyond risk to explore the experiences of serodiscordance tends to focus on tensions in such relationships, describing how couples struggle with numerous social, sexual, and emotional challenges and stressors (Kalichman 2000;VanDevanter et al 1999;Van der Straten et al 1998;Jarman, Walsh, and De Lacey 2005;Pomeroy, Green, and Van Laningham 2002;Knight et al 1997;Moore et al 1998;Remien et al 2003;Palmer and Bor 2001). The word itself, discordance, suggests disharmony and friction.…”
Section: Enacting Hiv-negativity: a Look At The Social Research Litermentioning
confidence: 96%
“…Dado que el malestar emocional en estas parejas guarda una estrecha relación con la satisfacción diádica, la satisfacción sexual, la autoinculpación y el apoyo de la propia pareja, sería necesario que las intervenciones clínicas para estas parejas se centraran en la relación y no en el enfermo por separado (Remien, Wagner, Dolezal y Carballo, 2003). De hecho ya disponemos de datos que hablan de la eficacia de programas como el de Pomeroy, Green y Van-Laningham (2002) que parten de esta idea.…”
Section: Retos Actuales En La Investigación Psicológica Sobre El Sidaunclassified